(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2016)
In this paper, an institutional diagnostic methodology for the Strategic Food Security Project (PESA-FAO) implemented in the Sierra Norte of the State of Puebla is being tested. Critical analysis of the formal and informal rules (institutions) that regulate the social interaction between the actors involved in the PESA and the way in which they generate incentives and behaviors that are counterproductive to the formal purpose of the PESA. Qualitative and quantitative research is conducted based on documentary and factual observation, as well as a standardized survey of beneficiaries and in-depth interviews with key informants. It is concluded that the factors that most negatively affect the performance of the PESA-FAO in the region studied are: a) conflict of interest between authorities, high bureaucracy, suppliers and Rural Development Agencies (ADR), which overlaps with the Formal purpose of thePESA; B) The negative incentives generated by the real contracting and re-contracting rules of field facilitators and Rural Development Agencies (ADR) focused on compliance with processes and loyalties and not on impacts; C) asymmetric information to the upper hierarchies on the management of local operators and the impacts they have on SPFS users; and d) insufficient and inadequate training of beneficiaries and ADR members.